SOCIAL PROBLEMS: A CASE STUDY OF STREET VENDOR CONTROL (PKL) AND WASTE MANAGEMENT - Wahyu Nurul Hidayati; Melly Agustina Permatasari; Sidharta Adyatma; Muhammad Yahya; Muhammad Andrie Iskandar (Universitas Lambung Mangkurat, 2026)
Handil Bakti, Barito Kuala Regency represents a critical intersection between vulnerable tidal wetland ecosystems and increasing urbanization pressures. This study analyzes the relationship between conflictive spatial planning policies, especially the control of street vendors (PKL), and ecological threats in the form of garbage accumulation on the Handil canal system. The research uses a qualitative approach with a case study method through triangulation of data obtained from direct observation and in-depth interviews. The results of the study show that street vendor control is still top-down and has not been accompanied by the provision of economically strategic relocation locations. This condition caused some street vendors to return to selling in prohibited areas, causing repeated social conflicts between the community and the local government. On the other hand, the dumping of plastic and styrofoam waste into the Handil canal by residents and trade activities causes a blockage of the two-way flow drainage system that functions to regulate the circulation of tide. The impact of these conditions can be seen in the increase in waterlogging in residential areas and the disruption of the hydrological function of wetlands, especially during the rainy season and during high tides. These findings show that the problem of spatial planning in wetland areas not only has an impact on the socio-economic aspects of informal communities, but also has direct implications for the increased risk of flooding, the decline in the quality of the residential environment, and the weakening of the ecological function of the Handil canal as a vital infrastructure in the swamp area. Therefore, spatial planning policies in wetland areas need to be designed in an integrated, participatory, and ecology-based manner by paying attention to environmental sustainability as well as the economic sustainability of local communities.